Applications of stable isotope analysis in zooarchaeology: An introduction - Zangrando, Atilio Francisco Javier (2014)
This special volume brings together works that present cases of studies that combine analysis of stable isotopes and zooarchaeology in different areas of Chile and Argentina, with special emphasis on the latter. These analyses were conducted in order to examine paleoecological conditions and interactions between humans and animal resources in different spatial and temporal contexts. In this introduction, we examine three ways in which stable isotopes have been applied in zooarcheology: (i) past animal-human relations, (ii) stable isotopes and zooarchaeology in conservation biology, and (iii) species biogeography, climate, and environment. The implications of the results of each of the papers in this volume stress that this type of study is a fruitful and promising line of research as it expands the thematic spectrum investigated, tests archaeological hypothesis, explores new lines of analysis, and enriches the interpretations about the past.